Research-Based Practical Applications for Utilizing Music to Increase Motivation and Physical Activity in Physical Education. (2nd January 2022) - Stephenson, Rachyl; Beddoes, Zack; Otterson, Steven; Rugen, Jacob
Abstract: This article explores current research on how music can affect levels of motivation and increase levels of physical activity. Some of the topics include using music as a distraction, thinking about synchronous or asynchronous pairing of music with lessons, and how the tempo may interact with student engagement. Following the review of current research on the topic, suggestions are provided on how to apply this research to utilizing music within physical education instructional practices.